Pengaruh Literasi Digital Dan Iklim Sekolah Terhadap Kreativitas Guru Di Gugus Langensari Dan Palasari Kecamatan Cijeruk Kabupaten Bogor - Junaedi, Yudi; Suciati, Suciati (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE INFLUENCE OF DIGITAL LITERACY AND SCHOOL CLIMATE ON TEACHERS' CREATIVITY IN THE LANGENSARI AND PALASARI GROUPS, CIJERUK DISTRICT, BOGOR REGENCYThe development of the quality of education is highly dependent on the ideas and creativity of teachers in it. Technological developments greatly influence today's education, so teachers must improve digital literacy skills, which are supported by the school climate as a support for the availability of creative space and time for teachers to carry out their duties. This study aims to find out, analyze, and describe the influence of digital literacy and school climate both partially and simultaneously on the creativity of elementary school teachers. This study was conducted on elementary school teachers in Langensari and Palasari Clusters, Cijeruk District, Bogor Regency with a population of 158 respondents and a sample of 113 respondents. This study uses a quantitative research method using questionnaires and interviews. The results showed that the value of the correlation coefficient between the variables of digital literacy and teacher creativity was 0.681 with a strong relationship level. The determination coefficient is 0.463, which means that digital literacy has a positive and significant effect on teachers' creativity by 46.30%, and other factors influence the rest. The correlation coefficient between school climate variables and teachers' creativity was 0.762, a strong relationship level. The determination coefficient is 0.581, which means that the school climate has a positive and significant effect on teachers' creativity by 58.10%, and other factors influence the rest. The value of the multiple correlation coefficient between digital literacy, school climate, and teacher creativity was 0.820, with an extreme correlation level. The coefficient of determination is 0.673, which means that digital literacy and school climate have a positive and significant effect on teachers' creativity by 67.30%, and other factors influence the rest.